HUBUNGAN MOTIVASI BERPRESTASI DENGAN PRESTASI BELAJAR MAHASISWA AKADEMI REFRAKSI OPTISI (ARO) YLPTK-PADANG - Mega Elfia (Ensiklopedia of Journal, 2020)
There are many factors affecting learning achievement include: external factors namely social environment and non social environment, factors of the consisting of physiological factors and psychological factors, and learning approach factors. One of important factors in an individual which pshycological factors affecting learning achievement is motivation to learn. With high motivation, then will get a high learning achievement too. This is research aims to know about the relationship between motivation to achievement with learning achievement. Design of this research is analytic, with use approach descriptive correlational.. Subject of this research is ARO student year 2018. Total sample of this research is 82 people and use total sample. Prossesing the statistical data for the relationship between motivation to learn with learning achievement use Spearman test. The result of this research show a significant relationship between motivation to achievement with learning achievement (r=0,243 p=0,213). In conclusion there was a relationship between motivation to achievement with learning achievement ARO student YPLTK Padang.